Modeling, Design, and Implementation of a Cloud Workflow Engine Based on Aneka - Jiantao Zhou; Chaoxin Sun; Weina Fu; Jing Liu; Lei Jia; Hongyan Tan (Journal of Applied Mathematics)
This paper presents a Petri net-based model for cloud workflow which plays a key role in industry. Three kinds of parallelisms in cloud workflow are characterized and modeled. Based on the analysis of the modeling, a cloud workflow engine is designed and implemented in Aneka cloud environment. The experimental results validate the effectiveness of our approach of modeling, design, and implementation of cloud workflow.